2022
DOI: 10.1186/s13071-022-05409-1
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of dengue in SAARC territory: a systematic review and meta-analysis

Abstract: Background Dengue is one of the common arboviral infections and is a public health problem in South East Asia. The aim of this systematic review and meta-analysis was to evaluate the prevalence and distribution of dengue in SAARC (South Asian Association for Regional Cooperation) countries. Methods The PubMed, PubMed Central, Embase and Scopus databases were searched for relevant studies. Statistical analysis on data extracted from the selected stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 77 publications
1
3
0
Order By: Relevance
“…Older adolescents and young adults also comprised the majority of the cases in 2016 (21-40; 55%), 2018 (15-29; 65%), and 2019 (21-40; 50%) outbreaks [12][13][14] . A similar result was reported in Sri Lanka in 2018 [15] and Ethiopia in 2017 16 . While studies conducted in different parts of India also noted a predominance of young adults [9], the first major dengue outbreak in Delhi in 1996 mainly affected the 5-12-year-old age group 17 .…”
Section: Resultsupporting
confidence: 87%
“…Older adolescents and young adults also comprised the majority of the cases in 2016 (21-40; 55%), 2018 (15-29; 65%), and 2019 (21-40; 50%) outbreaks [12][13][14] . A similar result was reported in Sri Lanka in 2018 [15] and Ethiopia in 2017 16 . While studies conducted in different parts of India also noted a predominance of young adults [9], the first major dengue outbreak in Delhi in 1996 mainly affected the 5-12-year-old age group 17 .…”
Section: Resultsupporting
confidence: 87%
“…The World Health Organization (WHO) revised dengue case classification, where severe dengue cases were reported to contain severe plasma leakage leading to dengue shock syndrome and fluid accumulation with respiratory distress, severe bleeding, and severe organ involvement, including the liver (AST or ALT ≥ 1000) and central nervous system, which may cause impaired consciousness, and other organs including heart, and occasional death may occur [ 29 , 30 ]. In SAARC (South Asian Association for Regional Cooperation) countries, the case fatality has been reported to be 1.9% of dengue cases [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…While a prevalence of NS1 antigenaemia as high as 35% is seen in all age febrile patients in Nigeria 26 , a prevalence as low as 2.2% in the same nation 27 is reported that is compatible with our observation. An NS1 antigen prevalence of 24.1% is shown in a systematic review among dengue suspected cases in Southeast Asia 28 . Overall, the findings suggest that dengue, as an endemic and epidemic-prone arboviral infection, likely plays a varying role as a cause of illness in both place and time.…”
Section: Discussionmentioning
confidence: 96%